Modeling and Contact Strength Analysis for Modified Cylindrical Gear Profile with Arcuate Tooth Trace - Zhang Haiyan; Hou Li; Wei Yongqiao; He Linli; Li Bo (Jixie chuandong)
Based on analyzing the meshing theory of ideal gear and the tooth surface equation,the tooth surface equation of modified cylindrical gear profile with arcuate tooth trace is deduced. The modeling of modified cylindrical gear profile with arcuate tooth trace is realized based on UG. The change curve of contact stress with different modification coefficient is obtained through the comparing and analyzing the contact stress of different modification with help of the ANSYS Workbench（AWE）. The result shows that the value of contact stress decreases with the increase of modification coefficient. When the modification coefficient over 0. 2,the trend of the contact stress decreasing remained unchanged,the theory basis for the design of modified cylindrical gear with arcuate tooth trace is provided by this results.